ROLE OF GREEN ENTREPRENEURSHIP IN RAISING THE EFFECT OF GREEN VALUE TOWARD SUSTAINABLE DEVELOPMENT - Nuringsih, Kartika (International Journal of Economics, Business, and Entrepreneurship, 2020)
In line with circular economic, the role of green entrepreneurship (GE) should be useful in preserving environmental sustainability. However, so many people are less aware of the importance of sustainability and green behavior in business activities. Therefore, the goal of the study is to explore a linkage of green value, GE, and sustainable development that is perceived by entrepreneurship students in Jakarta, Indonesia. 180 students were involved as respondents resulting in significant impacts. By using Smart-PLS proves significant relationships and finds a mediating effect of GE which links green value to sustainable development at the level of 5 percent. It forms a green triangle approach in promoting sustainability education for university students so that this linkage signs a good perception of students in expressing green value toward GE and sustainability issues. It is an early stage in promoting the triple bottom line so that the learning system could collaborate with stakeholders for enhancing the sustainability system in entrepreneurial education.